Mmu-miR-25-3p promotes macrophage autophagy by targeting DUSP10 to reduce mycobacteria survival - Yuan, Wenqi; Zhan, Xuehua; Liu, Wei; Ma, Rong; Zhou, Yueyong; Xu, Guangxian; Ge, Zhaohui (Frontiers in Cellular and Infection Microbiology, 2023)
Background The present study aimed to investigate the regulation of miR-25-3p on macrophage autophagy and its effect on macrophage clearance of intracellular Mycobacterium bovis Bacillus Calmette-Guerin (BCG) retention based on the previous findings on the differential expression of exosomal miRNA in macrophages infected with BCG. Methods Through enrichment analysis and Hub gene analysis, key differentially expressed miRNA and its target genes were selected. The targeted binding ability of the screened mmu-miR-25-3p and its predicted target gene DUSP10 was determined through the TargetScan database, and this was further verified by dual luciferase reporter gene assay. mmu-miR-25-3p mimics, mmu-miR-25-3p inhibitor, si-DUSP10, miR-NC,si-NC and PD98059 (ERK Inhibitor) were used to intervene macrophages Raw264.7. Rt-qPCR was used to detect the expression levels of mmu-miR-25-3p and DUSP10 mRNA. Western blot was used to detect the expression levels of DUSP10, LC3-II, p-ERK1/2, beclin1, Atg5 and Atg7. The autophagy flux of macrophage Raw264.7 in each group was observed by confocal laser microscopy, and the expression distribution of DUSP10 and the structure of autophagosomes were observed by transmission electron microscopy. Finally, the intracellular BCG load of macrophage Raw264.7 was evaluated by colony-forming unit (CFU) assay. Results Bioinformatics analysis filtered and identified the differentially expressed exosomal miRNAs. As a result, mmu-miR-25-3p expression was significantly increased, and dual specificity phosphatase 10 (DUSP10) was predicted as its target gene that was predominantly involved in autophagy regulation. The dual luciferase reporter gene activity assay showed that mmu-miR-25-3p was targeted to the 3’-untranslated region (UTR) of DUSP10. The infection of BCG induced the upregulation of mmu-miR-25-3p and downregulation of DUSP10 in RAW264.7 cells, which further increased the expression of LC3-II and promoted autophagy. Upregulated mmu-miR-25-3p expression decreased the level of DUSP10 and enhanced the phosphorylation of ERK1/2, which in turn upregulated the expression of LC3-II, Atg5, Atg7, and Beclin1. Immuno-electron microscopy, transmission electron microscopy, and autophagic flux analysis further confirmed that the upregulation of mmu-miR-25-3p promotes the autophagy of macrophages after BCG infection. The CFU number indicated that upregulated mmu-miR-25-3p expression decreased the mycobacterial load and accelerated residual mycobacteria clearance. Conclusion mmu-miR-25-3p promotes the phosphorylation of ERK1/2 by inhibiting the expression of DUSP10, thus enhancing the BCG-induced autophagy of macrophages. These phenomena reduce the bacterial load of intracellular Mycobacterium and facilitate the clearance of residual mycobacteria. mmu-miR-25-3p has great potential as a target for anti-tuberculosis immunotherapy and can be the optimal miRNA loaded into exosomal drug delivery system in future studies.